Discovery and efficacy study of an ALK inhibitor AMX6001 in anaplastic large cell lymphoma Karpas299 mice models - Debasis Das; Lingzhi Xie; Dandan Qiao; Yuxi Cao; Jianhe Jia; Yong Li; Jian Hong (Elsevier, 2024)
Anaplastic lymphoma kinase (ALK) is an attractive therapeutic target for the treatment of anaplastic large cell lymphoma (ALCL). We identified novel deuterated 2,4-diarylamino pyrimidine compounds as potent ALK inhibitors. The compound 9 (AMX6001) showed better in vitro activity against ALK and NPM-ALK kinase and significantly inhibited proliferation of Karpas299 and SU-DHL-1 cell lines. In vivo efficacy of compound 9 was better than reference standard ceritinib in ALCL Karpas299 mice models. Daily oral treatment of compound 9 (25 mg/kg) induced tumor suppression TGI up to 95.8 % in ALCL models.